2019
DOI: 10.1093/ajcn/nqz184
|View full text |Cite
|
Sign up to set email alerts
|

Folate status in the US population 20 y after the introduction of folic acid fortification

Abstract: Background Enriched cereal-grain products have been fortified in the United States for >20 y to improve folate status in women of reproductive age and reduce the risk of folic acid–responsive neural tube birth defects (NTDs). Objectives Our objectives were to assess postfortification changes in folate status in the overall US population and in women aged 12–49 y and to characterize recent folate status by demographic group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 25 publications
0
26
1
Order By: Relevance
“…In our study, the prevalence of folate insufficiency was highest in the first trimester, decreasing throughout pregnancy and the late start of folate supplementation may explain the discrepancy with previously reported postpartum folate status. Lower prevalence of folate insufficiency (assay-specific cut-off of <748 nmol/L, which is equivalent to the WHO cut-off of 906 nmol/L) of 18.6% has been reported in 12-49-year-old women in the US [27], where mandatory folate fortification of enriched cereal grain products has been in place since 1998 [28]. A German study conducted between 2008 and 2011 reported that 86% of the adult population, and 88.2% of the female population, was sufficiently supplied with folate [29].…”
Section: Discussionmentioning
confidence: 92%
“…In our study, the prevalence of folate insufficiency was highest in the first trimester, decreasing throughout pregnancy and the late start of folate supplementation may explain the discrepancy with previously reported postpartum folate status. Lower prevalence of folate insufficiency (assay-specific cut-off of <748 nmol/L, which is equivalent to the WHO cut-off of 906 nmol/L) of 18.6% has been reported in 12-49-year-old women in the US [27], where mandatory folate fortification of enriched cereal grain products has been in place since 1998 [28]. A German study conducted between 2008 and 2011 reported that 86% of the adult population, and 88.2% of the female population, was sufficiently supplied with folate [29].…”
Section: Discussionmentioning
confidence: 92%
“…Plasma and red blood cell (RBC) concentration also depends on the person’s ethnical group. For example, Non-Hispanic whites possess a 1,180 nmol/L RBC concentration in contrast to Non-Hispanic African Americans who have a 906 nmol/L ( Pfeiffer et al., 2019 ). On the other hand, pregnant women who were taking 400 mcg of FA per day can reach a concentration of 2,862 nmol/L in RBC at delivery ( Plumptre et al., 2015 ).…”
Section: Folic Acidmentioning
confidence: 99%
“…Fortification has been shown, through nationally representative dietary surveys, to relate to a consumption of about one‐third the RDA of synthetic folic acid from required fortification in “enriched” cereal grains (Yang et al, 2010). This intervention has not only resulted in a consistent improvements the mean blood folate concentrations among women of reproductive age to levels adequate enough to prevent FAP SBA (Pfeiffer et al, 2019), but also a significant reduction in the prevalence of FAP SBA, as shown through robust postfortification birth defects surveillance data nationally (Williams et al, 2015). Similar effect has been noted in Canada (De Wals et al, 2008).…”
Section: Discussionmentioning
confidence: 99%